Peningkatan Hasil Belajar PKN Melalui Model Pembelajaran Controversial Issues Pada Peserta Didik Di Kelas VIII SMP Negeri 2 Bambang Kabupaten Mamasa - Ahmad Al Yakin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2016)
Civics learning problems in class VIII SMP Negeri 2 Bambang lies in learning model that is less able to generate the critical thinking skills of learners. The purpose of this study is; Civics improve learning outcomes through learning model Controversial Issues in Class VIII students SMP Negeri 2 Bambang Mamasa, the type of research is classroom action research, consisting of four stages; 1) planning; 2) implementation; 3) observation; and 4) reflection. Subject of the study a total of 29 people. Data collection instruments used were Observation Sheet. Problem Tests and, Dokumentasi. Teknik descriptive statistics are used to describe the study variables, such as Mean (average value), Range (interval data), Minimum Score (lowest score) and Maximum Score (highest score) and percentage. The results showed that by using model Controversial Issues in teaching civics can increase the average value of students from the first cycle to silklus II. The mean value obtained by students in the first cycle of 73.79 at the high category of 89.6% with classical completeness of 62.1%. While on the second cycle increased the value of the average grade of 83.45 at the high category amounted to 75.9% with classical completeness of 100%.